Pengaruh Leverage terhadap Profitabilitas dan Return Saham dengan Intervening Asset Growth - Akhmad Syarifudin (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
Fundamental factor analysis is important to determine the company's performance. The purpose of this study is to determine the effect of leverage on profitability & stock prices through Asset Growth. The population of 664 issuers used 300 purposive samples covering all sectors on the 2011-2019 BEI. The research method uses SEM-Smart PLS path analysis. The results in group I (DAR <50%) DAR had a positive effect on AG; negative to ROA; and does not affect ROE; Meanwhile, AG affects ROE&PBV. The result of an indirect relationship AG mediates DAR to RS through ROE, but AG does not mediate DAR to RS through PBV. Shows an increase in debt increases asset growth and dividends, and if the increase in asset growth without increasing debt will increase dividends and stock prices. The results in group II (DAR>50%) DAR had a negative effect on AG&ROA, but did not affect ROE. While AG affects PBV, but does not affect ROE. The result of an indirect relationship AG mediates DAR to RS through PBV, but AG does not mediate DAR to RS through ROE. It shows that an increase in debt will reduce asset growth but will not affect dividends and vice versa, while an increase in asset growth will increase stock prices. This finding proves that the optimal capital structure is effective in improving company performance on the Indonesia Stock Exchange. Companies that have low debt and experience asset growth tend to produce high profitability and their share prices increase